Peranan Awig-awig Desa Adat dalam Konservasi Jalak Bali di Kepulauan Nusa Penida - Sudaryanto, F.X.; Pudyatmoko, S.; Subagja, J.; Djohan, T.S. (Jurnal Kajian Bali (Journal of Bali Studies); Vol 9 No 1 (2019): WACANA KRITIS BUDAYA BALI, 2019)
Bali Starling (Leucopsar rothschildi Stresemann, 1912) is an endemic bird in Bali, which is categorized as critical (Critically endangered). Starting in 2006 Bali starling conservation efforts were also carried out in the Nusa Penida Islands. This study aims to study contribution of the customary village regulation (awig-awig) to the success of the conservation of Bali Starling in the Nusa Penida Islands. Methods used included calculation of the Bali starling population directly with concentrated methods and the awig-awig implementation in the community obtained using AHP (Analytical Hierarchy Process). Results of the study showed that the population of Bali Starling in 2006 was 49, while in 2015 there were 66 individuals. Awig-awig has been the most important alternative to protect Bali starling. The conclusion of this study is that the Bali Starling population is increasing, and the Nusa Penida Islands community has a perception, and good participation in the awig-awig who protect the Bali Starling.